If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 2x + 1 Reorder the terms: -8 + 6x = 2x + 1 Reorder the terms: -8 + 6x = 1 + 2x Solving -8 + 6x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 6x + -2x = 1 + 2x + -2x Combine like terms: 6x + -2x = 4x -8 + 4x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 4x = 1 + 0 -8 + 4x = 1 Add '8' to each side of the equation. -8 + 8 + 4x = 1 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = 1 + 8 4x = 1 + 8 Combine like terms: 1 + 8 = 9 4x = 9 Divide each side by '4'. x = 2.25 Simplifying x = 2.25
| 49+7x=21 | | 2ln(x)-ln(2x-5)=ln(7x)-ln(x+2) | | 300*.10=5 | | 10x+4-2x=8 | | 4cotx+1=5 | | 2400-160x+2x^2=1312.5 | | 7r^2+5r+3=0 | | 8s^2-22s+5=0 | | (x+0.5)(x+3.4)=0 | | 2.16b+5=1.6b+10 | | 144= | | 144=12 | | 2(2z-2)-2(4-2z)=2 | | 3x+15+39=90 | | 12r^2+3=0 | | 3x+15+39=180 | | 7x-16=-1 | | 8-3=10y | | -2x+1-(-3x+3)=-4+(-x-2) | | 0.8=0.2y+3.4 | | 5t-23=-23+7t | | 9x+19=-26 | | -3p-5-p-(-3p)+4p+7p+5= | | 4x^3-40x^2+96x=0 | | 2t-22=-16+5t | | 4x^3-9x^2+2=0 | | 4(d+5)-26= | | k^2+5k-20=0 | | 4.5=x+1.6 | | 7x^2-2x-13=0 | | -7x+9=1-7x | | 5(3y-2)+8=48 |